A Study on Tax Literacy among Salaried Individuals - Bibay, Pooja; Kumar, Dr Pradeep (The journal of contemporary issues in business and government, 2023)
Aim. The taxpayer's knowledge has a significant impact on the degree of compliance with tax law, tax planning, and tax management. It improves tax collection by the states as Taxation is an extremely important aspect in any country being the state's primary source of revenue. Method: This study used a convenience sampling method with size of 147. The data has been ANOVA tested to examine the current tax literacy level among salaried people and also to determine how a demographic element affects the tax knowledge of salaried people. Results. In this study, 74% male and 26% Female respondents participated. Both have equal tax literacy. The respondents belong to different age criteria. Individuals of age 18-30 yeras are better on tax literacy as compared to the other age criterion individuals. The respondents of the age category of 60 & above years are having less tax-related literacy. Conclusion. Tax literacy is one of the financial literacy dimensions financial knowledge. Taxpayers with higher age groups find it challenging to comprehend and understand difficulties relating tax liability, filing or saving taxes. The younger age group was found to be better literate and follow tax-related issues closely, irrespective of gender.